MINERALS – INDICATORS OF CONDITIONS OF THE MODERN RIVER SEDIMENTOGENESIS - Belitska, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
About hundred samples of modern alluvium of rivers in Central and Southern Ukraine: Dnieper, Southern Bug, Ingul, Ingulets and their tributaries are studied on their mineral compositions, structure and technological properties. River sediments contains a wide range of fragments from boulders in the upper reaches to pelitomorphic silt in delta areas. Sands and silts are the dominant varieties. Sediment composed of quartz and other silicates, carbonates, various oxides, sulfides, less sulfates, native minerals. In the estuarine areas of rivers identified high concentrations of almandine, ilmenite, zircon, monazite, to a lesser extent – apatite, rutile, gold and other minerals. A separate group of minerals form in the sediment micro spherulites, euhedral crystals, friable aggregates of needle-like crystals of microscopic size. These are barite, hematite, pyrite, marcasite, gypsum, carbonates. In their formation are involved processes of chemical deposition, substitution and biomineralogy. Identified the areas of pollution of alluvium by industrial waste, as a result of activity of enterprises on the catchment of rivers. The products of mining, metallurgical, machine-building, chemical and other industries fall into the river sediments. In some areas of rivers occurred enrichment of alluvium by technical minerals, and their concentration corresponds to poor ores. Fron the territory of settlements and enterprises to surface waters with sand and clay enters also oil. Transportation of wastes occures along the system of gullies and ravines that enter into the river network. They are the most contaminated elements of modern geological environment. Thus, river sedimentation differentiation and industrial activity are factors of modern river mineralization. Industrial production and urban catchment area have occurred to be the reason of fundamental changes in the natural state of rivers. Distributed its in mineral paragenesis and associations of alluvium have become sensitive indicators of condition of ecosystem. Completed studies indicate polygenic (natural and manmade) formation of high concentrations of heavy minerals and the possibility of integrated use of modern river sediments fot the the improvement of the environment sittuation. This allows to determine the genesis of mineralization, provides the necessary information about the technological properties of sedimentary ores and the methods of separation, creates conditions for the improvement of the ecological environment.